Linguistic Forms and Functions of Rhetorical Strategies in the Sermons of Selected Pentecostal Churches in Lagos (2015)
The language of Pentecostal sermons often features communicative function seeking to persuade, exhort and influence the audience. Previous linguistic studies on Pentecostal sermons, using stylistic perspective, have focused on content and tenor, emphasising the personal tenor of the discourse in terms of speaker as the „knower‟, and the audience as the non-„knower‟, but have not given adequate attention to their rhetorical strategies as persuasive communication. This study, therefore, examined selected Pentecostal sermons in Lagos with a view to identifying the linguistic forms and functions of their rhetorical strategies and persuasive value for a full understanding of the language of Nigerian Pentecostalism. This study adopted a synthesis of insights from Aristotelian rhetoric, Halliday‟s Systemic Functional Linguistics, and Lakoff and Johnson‟s Conceptual Metaphor Theory as the theoretical framework. Twenty five sermons, five from each of the selected five Pentecostal churches: The Redeemed Christian Church of God (RCCG), Deeper Life Bible Church (DLBC), Living Faith Church (LFC), Mountain of Fire and Miracles Ministries (MFM) and Believers‟ Love World (BLW) were purposively selected for their rhetorical content and appeal. Two hundred copies of a questionnaire, constructed to authenticate the persuasive value of the identified rhetorical strategies were administered to a cross-section of members of the five churches (old-50, young-50, male-50, and female-50). The sermons, produced between 2005 and 2011, and orally delivered and recorded on audio formats, were transcribed and processed. Data were subjected to linguistic and rhetorical analyses and represented in percentages. An average of three major linguistic forms of rhetorical strategies – metaphors (70.8%), rhetorical questions (26.5%) and proverbs (2.7%) were identified. Concept-based metaphors invoke causality, spirituality, prosperity, emotion and warfare. Logos-based metaphorical argumentation that featured cause and effect (“Sowing is reaping”) expounds familiar spiritual truths. Similarly, the metaphor “Poverty is a disease” instills prosperity consciousness in a harsh socio-economic situation, while metaphors of battlefield (“Christianity is warfare”) emphasises spiritual warfare against Satan. Strategies of coercion (ordering/commanding and warning/threatening) are linguistically encoded in interrogatives, imperatives and declaratives (“If you sin, you die”). Ethicallybased proverbs enact moral truths to warn and advise Christians, and also regulate social behaviour. Rhetorical questions (Wh-“What does God want?” and polar - “Is God a liar?”) contain unverbalised answers meant to appeal to emotion. Lexical choices like “liar”, “oppressor” and “evil”, and flyting, deployed as vituperation (“Yeye Satan”) express emotions of anger and hatred against the enemy, while personal pronouns, “we” and “they” are deployed to polarise believers and non-believers. Members (50.5%) were highly persuaded by metaphors rooted in their indigenous cultures and languages, while 26% felt persuaded by rhetorical questions, and 23.5% less persuaded by the use of proverbs. The MFM uses more conceptual metaphors of warfare than other churches, while LFC, DLBC and RCCG use more rhetorical questions than MFM and BLW. Metaphors, rhetorical questions and proverbs are the linguistically explicated forms of rhetorical strategies for persuasion in Nigerian Pentecostal sermons. Awareness of these linguistic forms is essential for an understanding of the language and rhetoric of Nigerian Pentecostalism